Strategi Pengembangan Produk Hasil Hutan Bukan Kayu (HHBK) Tanaman Aren (Arenga Pinnata) pada Kesatuan Pengelolaan Hutan Pulau Laut Sebuku - Mustaqim, Musaddak; Rahayu, Dewi (PPJP ULM, 2022)
This study aims to determine the development strategy of aren plant products and the condition of palm farmers in Forest Management Units (KPH) Pulau Laut Sebuku. The data sources of this research are secondary data using documentation from the South Kalimantan Provincial Forestry Service and documentation data from Forest Management Units (KPH) Pulau Laut Sebuku. Primary data collection techniques are obtained through interviews with Forest Management Units (KPH) Puau Laut Sebuku with a structured questionnaire. The technique used is descriptive statistical analysis using cross tabulation to see the condition of farmers and SWOT analysis aims to determine the strategy for developing palm oil NTFP products that are more appropriate to the conditions and potential of the existing area. The results showed that the farming conditions of palm sugar still need to be improved in terms of developing NTFP products so that farmers can compete with other commodities. The development strategy is the S-O strategy, which is to use strength to take advantage of opportunities so as to make development policies that are right on target, namely developing public interest in advancing in order to increase the food industry made from palm sugar and increase the potential as a regional superior product with the role of local governments in the development of palm trees.